THE EFFECT OF USING 4 POINTS LOCKS AND 9 POINTS LOCKS MASKS ON PATIENT SET-UP IN NASOPHARYNX CANCER - Anggraeni, Rina; Irsal , Muhammad; Sutoro, Shinta Gunawati; Widiatmoko, Mahfud Edy; Tarigan, Asumsie; Ardoni, Fitrus; Apriantoro, Nursama Heru (Indonesian Physical Review, 2024)
The set-up aims to find out the value of the shift that occurs while the patient is undergoing the irradiation process on the X-axis (right-left), Y-axis (caudal-cranial), and Z-axis (anterior-posterior). The procedure for collecting research data is by making direct observations and being involved in measuring set-up shifts. The data used amounted to 20 nasopharyngeal cancer patients. Set-up shift measurement data were taken sequentially from fractions 1-33 for each patient using 4 and 9 points locks masks. Analysis of statistical test data using SPSS version 25, to determine the effect of using 4 and 9 points locks masks on shifts in nasopharyngeal cancer irradiation set-up patients with fraction group: Group 1 (fraction 1), Group 2 (Fraction 2 – 15), Group 3 (16-33)  using the Wilcoxon test because the normality test results were not fulfilled. If the p-value ≤ 0.05, there is an effect of using 4 and 9 points locks mask on shifts, while for p-value ≥ 0.05, there is no effect of using 4 and 9 points locks mask on set-up shifts in nasopharyngeal cancer irradiation set-up. The results of the shift in the set-up of 4 and 9 points lock irradiation vertically in the lateral, longitudinal, and vertical directions tend to be positive (left, caudal, posterior). There was no effect of all fraction groups using 4 and 9 points locks on the shift in nasopharyngeal cancer irradiation set-up p-value> 0.05.